Generation I(mmersion) – How to Meet Learner Expectations of Tomorrow - Erenli, Kai (International Journal of Advanced Corporate Learning (iJAC), 2016)
Today’s teachers mainly belong to the so-called “Generation X” while learners are most often described as “Generation Y” or “Millennials”. Most current discussions of learning methods are being held in view of the status quo. But what about the learners of tomorrow? What expectations do the learners of tomorrow have? Which methods and tools will the teachers of tomorrow have in stock to meet these expectations? “The old learning spaces, dominated by the immensely successful organizations of the industrial era like schools and universities, are struggling to maintain authority and control over the definition and certification of knowledge while at the same time remaining true to the stated mandate of helping to equip people and society for a life where learning is much more heterogeneous and heterarchical”[11]. Therefore, wouldn´t it be good to have a toolset ready and be able to choose the appropriate tools and techniques right on time? Reflecting on publications, expert interviews and state-of-the-art best practices, this paper attempts to draw a picture of the future (e-)learning scenario. To give the next generation a name, “Generation I(mmersion)” has been chosen. Despite breaking the X, Y, Z sequence, this name highlights the state of “Immersion”, which educators and learners of tomorrow will/might find themselves in.